Prevention and Control of Nosocomial Infections Through Implementation of Precaution Standards at Royal Prima Hospital Medan - Pesta Ria, Anna Maria; Ginting, Chrismis Novalinda; Nasution, Sri Wahyuni (Buletin Farmatera, 2024)
Abstract: Nosocomial infections (Health Care-Associated Infections/HAIs) are infections that occur in sufferers, health workers, and also everyone who comes to the hospital. There are six types of nosocomial infections, namely: HAP/VAP infections, Phlebitis, urinary tract infections (UTI), surgical wound infections, primary bloodstream infections, and decubitus ulcers. Efforts to prevent nosocomial infections are carried out through the Infection Prevention and Control (IPC) program by implementing Standard Precautions in health facilities, including hospitals. One of the implementations of standard precautions is maintaining hand hygiene. This research is a type of quantitative research with a case-control design conducted at the Royal Prima Medan Hospital on IPC officers with a sample size of 50 respondents who used a questionnaire as a research instrument consisting of three types, namely: Knowledge, Attitude, and Practice adapted from the WHO Hand Hygiene Knowledge Questionnaire for Health Care Workers. Validity tests and reliability tests on the three types of questionnaires show that all questions are valid and reliable. The analysis carried out in this research included three forms, namely: univariate, bivariate and multivariate analysis, using the IBM SPSS version 29 program.